Jack Irish. Season 2 [videorecording (DVD)] - Pearce, Guy, 1967-; Dusseldorp, Marta, 1973-; Pederson, Aaron; Temple, Peter, 1946-2018 (Acorn : RLJ Entertainment, 2018)
When an Australian aid-worker is kidnapped by Muslim extremists, a high-stakes race to save his life pits East against West in these exciting new episodes. From the island of Mindanao in the Philippines to Melbourne, Jack Irish is caught in a global web of religious zealotry among right-wing Christians and media-savvy jihadists.